Genetic dissection of region around the Sa gene on rat chromosome 1: evidence for multiple loci affecting blood pressure. - Frantz, S; Clemitson, JR; Bihoreau, M; Gauguier, D; Samani, N (2001)
A region with a major effect on blood pressure (BP) is located on rat chromosome 1 in the vicinity of the Sa gene, a candidate gene for BP regulation. Previously, we observed a single linkage peak for BP in this region in second filial generation rats derived from a cross of the spontaneously hypertensive rat (SHR) with the Wistar-Kyoto rat (WKY), and we have reported the isolation of the region containing the BP effect in reciprocal congenic strains (WKY.SHR-Sa) and (SHR.WKY-Sa) derived from these animals. Here, we report the further genetic dissection of this region. Two congenic substrains each were derived from WKY.SHR-Sa (WISA1 and WISA2) and SHR.WKY-Sa (SISA1 and SISA2) by backcrossing to WKY and SHR, respectively. Although there was some overlap of the introgressed regions retained in the various substrains, the segments in WISA1 and SISA1 did not overlap. Furthermore, although the Sa allele in WISA1, WISA2, and SISA2 remained donor in origin, recombination in SISA1 reverted it back to the recipient (SHR) allele. Surprisingly, all 4 substrains demonstrated a highly significant BP difference compared with that of their respective parental strain, which was of a magnitude similar to those seen in the original congenic strains. The findings strongly indicate that there are at least 2 quantitative trait loci (QTLs) affecting BP in this region of rat chromosome 1. Furthermore, the BP effect seen in SISA1 indicates that at least a proportion of the BP effect of this region of rat chromosome 1 cannot be due to the Sa gene. SISA1 contains an introgressed segment of <3 cM, and this will facilitate the physical mapping of the BP QTL(s) located within it and the identification of the susceptibility-conferring genes. Our observations serve to illustrate the complexity of QTL dissection and the care needed to interpret findings from congenic studies.